2008
DOI: 10.1097/tp.0b013e318180731e
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy With Methyl Aminolevulinate for Prevention of New Skin Lesions in Transplant Recipients: A Randomized Study

Abstract: Our results suggest that repeated field photodynamic therapy using topical MAL may prevent new AK in transplant recipients although further studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 34 publications
2
72
1
2
Order By: Relevance
“…BCC is the commonest skin cancer and superficial lesions are often low risk but multiple. PDT is an effective treatment modality for large, multiple, superficial, low risk tumours, field carcinogenesis or dysplasia, as well as in cases when repeated treatments are needed 3 such as immunosuppressed patients, including organ transplant recipients 5 . AK and sBCC respond better to PDT than nodular BCC, arguably due to the fact that the prodrug used is taken up and metabolised more efficiently in the superficial layers of skin than in deeper layers 6 .…”
Section: Introductionmentioning
confidence: 99%
“…BCC is the commonest skin cancer and superficial lesions are often low risk but multiple. PDT is an effective treatment modality for large, multiple, superficial, low risk tumours, field carcinogenesis or dysplasia, as well as in cases when repeated treatments are needed 3 such as immunosuppressed patients, including organ transplant recipients 5 . AK and sBCC respond better to PDT than nodular BCC, arguably due to the fact that the prodrug used is taken up and metabolised more efficiently in the superficial layers of skin than in deeper layers 6 .…”
Section: Introductionmentioning
confidence: 99%
“…102,103 In addition, over the course of 1 year, a single session of MAL-PDT significantly delayed the appearance of new lesions relative to placebo treatment. 104 Over the longer term (≥2 years), MAL-PDT did not appear to reduce the incidence of AKs 105 or SCCs. 106 However, this discrepancy, relative to longer-term outcomes with ALA-PDT, 101 may be explained in part by less frequent follow-up sessions in the MAL-PDT studies.…”
Section: Aks In Organ Transplant Recipientsmentioning
confidence: 99%
“…Treatment with cyclic ALA-PDT at 4-8 week intervals over a 2-year period on 12 organ transplant recipients led to a significant reduction of SCC (98% mean reduction) [107]. Wennberg et al [108] also found that repeat MAL-PDT treatments reduced the occurrence of new AKs in this special population.…”
Section: Squamous Cell Carcinomamentioning
confidence: 88%